COMPULSORY MADRASAH EARLY EDUCATION PROGRAM IN PASURUAN REGENCY: BETWEEN PUBLIC POLICY AND POLITICAL ORDERS - Safara Akmaliah; Muhammad Adnan; Laila Kholid Alfirdaus (Universitas Airlangga, 2023)
Research on the madrasah diniyah compulsory education program in Pasuruan Regency was conducted to reveal the relationship between public policy and the power of a particular religious group. A qualitative approach was applied to this research, by presenting facts that had been collected through several reports and in-depth interviews. Furthermore, the fact findings are analyzed based on the principles, concepts and theories of public policy. Research also relies on the results of existing research, especially research with similar material objects and similar perspectives. The focus of this research is to analyze the background of policy making, the dynamics of policy making, and program implementation. The results of this study indicate that the purpose of establishing the madrasah diniyah compulsory education program is to instill religious values to build morality and overcome crime. This research also confirms that regulations related to compulsory education at madrasah diniyah in Pasuruan Regency were formed because of the closeness between policy makers and Nahdlatul Ulama (NU) as a social organization. NU is the dominant force in social, cultural, and governmental politics. This research also clearly finds indications of policy exclusivity. The stipulated program only contains the interests of one group, thus reducing the power of other groups as elements that also live in the public sphere. Another implicative aspect is the increasing implementation of madrasah diniyah in Pasuruan district which is followed by an increase in the quality of teachers.